2019
DOI: 10.1111/njb.02558
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive systems and low outbreeding barriers between Jacaranda cuspidifolia and J. mimosifolia (Jacarandeae, Bignoniaceae)

Abstract: The genus Jacaranda shows notable karyotype stability and a prevailing self‐sterile breeding system with evidence of late‐acting self‐incompatibility in several species. However, some studies have indicated self‐compatibility in J. mimosifolia, a species cultivated worldwide in tropical and subtropical areas. Jacaranda cuspidifolia is a closely related species with natural distribution broadly overlapping with that of J. mimosifolia, and manual heterospecific pollination studies have indicated that these speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Unilateral cross-incompatibility(UCI) is defined as asymmetric reproductive isolation, manifested by successful crosses in one direction and unsuccessful crosses in the other ( Muñoz-Sanz et al., 2020 ). Currently, UCI has been observed in banana shrub ( Xu et al., 2017 ), jacaranda tree ( Bittencourt, 2019 ), azalea ( Okamoto and Ureshino, 2015 ), etc. However, no studies have been reported on the cytological mechanism of interspecific asymmetric hybridization in the genus Camellia between Camellia oleifera and Camellia yuhsienensis.…”
Section: Introductionmentioning
confidence: 99%
“…Unilateral cross-incompatibility(UCI) is defined as asymmetric reproductive isolation, manifested by successful crosses in one direction and unsuccessful crosses in the other ( Muñoz-Sanz et al., 2020 ). Currently, UCI has been observed in banana shrub ( Xu et al., 2017 ), jacaranda tree ( Bittencourt, 2019 ), azalea ( Okamoto and Ureshino, 2015 ), etc. However, no studies have been reported on the cytological mechanism of interspecific asymmetric hybridization in the genus Camellia between Camellia oleifera and Camellia yuhsienensis.…”
Section: Introductionmentioning
confidence: 99%
“…Anyway, obtainance of seeds may be complex, since the Bignoniaceae family is marked by floral self-incompatibility (Gandolphi and Bittencourt 2010). Regarding other species from Jacaranda genus, floral self-incompatibility was recorded for J. racemosa (Bittencourt and Semir 2006), J. copaia (Gurgel et al 2006, Jones and Hubbell 2006, Maues et al 2008, J. rugosa (Milet-Pinheiro & Schlindwen 2009), J. mimosifolia (Alves et al 2010, Bittencourt 2019, J. oxyphylla (Guimarães et al 2018), J. rugosa (Pontes et al 2022), while J. caroba showed some floral self-compatibility at a range of about 3% of self-pollinated flowers growing into mature fruits (Yanagizawa 1983, Guimarães et al 2008. The extension of floral self-incompatibility has not been recorded to Jacaranda ulei.…”
mentioning
confidence: 99%